Radiographic and visual response to the type II RAF inhibitor tovorafenib in children with relapsed/refractory optic pathway glioma in the FIREFLY-1 trial - Nysom, Karsten; Kilburn, Lindsay B; Leary, Sarah E S; Landi, Daniel B; de Vos-Kerkhof, Evelien; Perreault, Sébastien; Witt, Olaf; Ziegler, David S; Hernáiz Driever, Pablo; Franson, Andrea T; Baxter, Patricia A; Whipple, Nicholas S; et al. (Neuro-Oncology, 2024)
Due to their anatomical locations, optic pathway gliomas (OPGs) can rarely be cured by resection. Given the importance of preserving visual function, we analyzed radiological and visual acuity (VA) outcomes for the type II RAF inhibitor tovorafenib in the OPG subgroup of the phase 2 FIREFLY-1 trial.FIREFLY-1 investigated the efficacy (arm 1, n = 77), safety, and tolerability (arms 1/2) of tovorafenib (420 mg/m2 once weekly; 600 mg maximum) in patients with BRAF-altered relapsed/refractory pediatric low-grade glioma (pLGG). In this post hoc analysis, anti-tumor activity and VA were analyzed in arm 1 patients with OPG. Anti-tumor activity was independently assessed per Response Assessment in Neuro-Oncology high-grade glioma (RANO-HGG), Response Assessment in Pediatric Neuro-Oncology-LGG (RAPNO), and RANO-LGG criteria. The data cutoff was June 5, 2023.Forty-two of 77 patients had OPGs; 35 of 42 had ≥2 VA assessments. The overall response rate in the OPG subgroup according to RANO-HGG, RAPNO, and RANO-LGG criteria were 64%, 50%, and 55%, with clinical benefit rates of 95%, 88%, and 90%, respectively. VA per patient was preserved for 80% of patients; 31% demonstrated improved VA; VA per eye was preserved in 87%, with 27% improving. The safety profile in the arm 1 OPG subgroup was similar to the overall FIREFLY-1 safety analysis set.Tovorafenib demonstrated anti-tumor activity in relapsed/refractory BRAF-altered OPG across radiological assessment criteria and was generally well tolerated. Importantly, vision remained stable or improved in most patients.
Gesehen am 06.11.2025